E-comic physics development through PBL stages to improve students’ nature of science - Murni, Cahya Intan; Firdaus, Rangga; Rohman, Fatkhur; Pramudiyanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The 2019 TIMSS results revealed that Indonesian students' science achievement remains below the international average, reflecting low scientific literacy. This issue is partly attributed to conventional teaching methods that lack engagement and inquiry-based approaches. This study aimed to develop a digital learning medium, e-comic physics, based on Problem-Based Learning (PBL) to enhance elementary students’ understanding of the Nature of Science (NoS). Field observations at UPT SDN 3 Sumberejo revealed that 73% of teachers had not yet adopted interactive digital media, underscoring the study’s urgency. Employing a Research and Development (R&D) design with the Tessmer model, involving 60 students, the study used descriptive and inferential statistical techniques. The findings showed that the media was highly valid, very practical, and significantly effective, as evidenced by improved post-test scores and t-test results. The effect size analysis indicated a moderate to substantial impact on learning outcomes, confirming the media’s pedagogical potential in promoting scientific reasoning. In conclusion, the e-comic physics is a feasible and innovative learning tool for primary science education. Further research is recommended to examine its long-term effectiveness across broader subject matter.